LE CONTENU POLLINIQUE DE L’ATMOSPHERE DE LA VILLE D’EL HADJAR (ANNABA, ALGERIE) (Sciences & Technologie. C, Biotechnologies, 2006)
The present work consists in analysing the pollen content of the atmosphere of the El-Hadjar city (Annaba, Algeria) in view to know the qualitative and quantitative composition of the pollens and to achieve a pollen calendar. Gravimetric method has been used during seven months (March-September 1997). A total of 7190 pollen grains belonging to 16 plant families have been taken. However, the Poaceae family, causing hay fever, has represented by 21 % in which were counted. The pollen calendar shows that the May is the richest month with a total of 2321 grains (32,28 %), followed by April with a 1748 grains. Data confrontation of the pollen spectrum with those of climatic conditions revealed a positive interrelationship between the numbers of pollen collected the increase of the temperature and the wind speed. On the other hand, the interrelationship was negative between the number of pollen, the precipitation and the relative humidity. The importance of the pollen calendar resides in the air concentration of the allergenic pollens according to the time, due to the allergenic point response of the pollinic allergens, expressed by allergenic pollen number in 24 hours.